Effects of NaCl treatments on seed germination and antioxidant activity of canola (Brassica napus L.) cultivars - Shahbazi, E; Arzani, A; Saeidi, G (Bangladesh Journal of Botany, 2011)
Effects of salt stress on germination, seedling growth and activity of antioxidant enzymes in leaves of six cultivars of canola (Brassica napus L.) were investigated on two F1 hybrids (Hyola401, Hyola330) and four open pollinated cultivars (Zarfam, Okapi, RGs003 and Sarigol). Seeds were germinated under various levels of salinity (0, 50, 100, 150 and 200 mM NaCl solutions). An increase in NaCl concentrations progressively inhibited seed germination. Hyola401 showed the highest germination percentage at all salinity levels. Seedling growth parameters were affected by salt stress particularly at 150 and 200 mM. Leaf antioxidant activities of superoxide dismutase (SOD), ascorbate peroxidase (APX) and glutathione reductase (GR) were increased by salinity increase up to 150 mM while decreased at 200 mM NaCl concentration. Although constitutive levels of activity of antioxidative enzymes were almost the same among the canola cultivars, Hyola401 induced antioxidant enzyme activities were more efficient when subjected to NaCl treatment. Among the tested cultivars, F1 hybrid ‘Hyola401’ could be considered as salt tolerant as possessing higher germination percentage, better seedling growth and antioxidant activities under salinity stress. On the other hand, F1 hybrid ‘Hyola330’ performed inferior to said aspects and was the most susceptible cultivar to salinity stress. Key words: Canola; Brassica napus; Salinity; Antioxidant enzyme; NaCl; Germination DOI: http://dx.doi.org/10.3329/bjb.v40i1.8000 Bangladesh J. Bot. 40(1): 67-73, 2011 (June)